2013
DOI: 10.1017/s1751731113001419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of average litter weight in pigs on growth performance, carcass characteristics and meat quality of the offspring as depending on birth weight

Abstract: Offspring born from normal litter size (10 to 15 piglets) but classified as having lower than average birth weight (average of the sow herd used: 1.46 6 0.2 kg; mean 6 s.d.) carry at birth negative phenotypic traits normally associated with intrauterine growth restriction, such as brain-sparing and impaired myofiber hyperplasia. The objective of the study was to assess long-term effects of intrauterine crowding by comparing postnatal performance, carcass characteristics and pork quality of offspring born from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…The better FCR indicates that the greater ADG of heavy piglets was not achieved only because of their greater physical capacity to consume more feed. Pardo et al (2013) confirmed the relationship between growth rate and weaning weight depending on birth weight, and showed that lighter pigs took more days than the heavier pigs to reach market weight.…”
Section: Discussionsupporting
confidence: 58%
“…The better FCR indicates that the greater ADG of heavy piglets was not achieved only because of their greater physical capacity to consume more feed. Pardo et al (2013) confirmed the relationship between growth rate and weaning weight depending on birth weight, and showed that lighter pigs took more days than the heavier pigs to reach market weight.…”
Section: Discussionsupporting
confidence: 58%
“…The higher litter size observed here might result from differences in the genetic background of parent animals used and more generally from intensive breeding for increased ovulation rates and uterine capacity resulting in high litter size 37,38 . Negative effects of selection for larger litter sizes were stressed by various authors 5,14,39,40 , and include a general decrease in birth weight and an increased number of lightweight born piglets 7 . The mean birth weight observed in the present study showed a negative correlation (71%) to litter size.…”
Section: Discussionmentioning
confidence: 99%
“…After the carcass dissection was completed, and following the protocol described by Pardo et al [12], the longissimus thoracis muscle (LT) at the 10th rib level was removed for the determination of ultimate pH, meat color (L*, a, b* values), water holding capacity as a percentage drip after 24 h, and cooking and thaw loss and shear force. Briefly, five 2.5 cm chops weighing on average 80 g each were used.…”
Section: Meat Quality Traitsmentioning
confidence: 99%